A flower-like NiO–SnO2 nanocomposite and its non-enzymatic catalysis of glucose. Issue 71 (21st September 2017) - Zhou, Yan; Ni, Xiao; Ren, Zhen; Ma, Jiayi; Xu, Jinzhong; Chen, Xiaojun
Abstract : A flower-like NiO–SnO2 nanocomposite was synthesized by a solvothermal method, which exhibited highly non-enzymatic catalysis towards the oxidation of glucose with a linear response range of 0.01–26 mM and a detection limit of 1 μM. Abstract : A flower-like NiO–SnO2 nanocomposite (NSNF) with electrochemical activity was synthesized by a solvothermal method. The morphology and composition of the NSNF have been characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM) and X-ray diffraction (XRD). The synthesized NSNF was immobilized onto the surface of an indium tin oxide (ITO) electrode and exhibited highly non-enzymatic catalysis towards the oxidation of glucose. The effect of NaOH concentration on the oxidation performance of glucose was investigated. Under the optimum conditions, the catalytic current showed a linear relationship with the increase of glucose concentration in the range of 0.01–26 mM, with a detection limit of 1 μM. The excellent sensing performance can be attributed to the unique porous architecture of NSNF, which enhanced the electron transfer during the electrochemical sensing of glucose. The glucose sensor also had a high selectivity for glucose detection, which could effectively resist the interference from ascorbic acid (AA), uric acid (UA), citric acid (CA), hydrogen peroxide (H2 O2 ) and even other carbohydrates, such as fructose, sucrose and maltose. Finally, the glucose sensor was also used for glucose detection in real human serum samples and the results were satisfactory.